Extreme hypofractionated stereotactic radiotherapy for localized prostate Cancer: Efficacy and late urinary toxicity according to transurethral resection of the prostate history - Maxime Galienne; Séverine Risbourg; Thomas Lacornerie; Alexandre Taillez; Eric Lartigau; Maël Barthoulot; David Pasquier (Clinical and Translational Radiation Oncology, 2024)
Background and purpose: Extreme hypofractionated stereotactic body radiotherapy (SBRT) is a therapeutic alternative for localized low- or intermediate-risk prostate cancer. Despite the availability of several studies, the toxicity profile of SBRT has not been comprehensively described. This real-world evidence study assessed the efficacy and toxicities associated with this regimen, and potential prognosis factors for genitourinary toxicities. Materials and methods: This retrospective study included 141 consecutive patients with localized prostatic adenocarcinoma treated with CyberKnife™ SBRT, as primary irradiation, at the Oscar Lambret Center between 2010 and 2020. The prescribed dose was 36.25 Gy in 5 fractions. Acute and late toxicities were graded according to the CTCAE (version 5.0). Biochemical recurrence-free survival (bRFS) and overall survival (OS) were estimated using the Kaplan–Meier method. The cumulative incidence of biochemical recurrence (cBR) was estimated using the Kalbfleisch–Prentice method. Results: Among the included patients, 13.5 % had a history of transurethral resection of the prostate (TURP). The median follow-up was 48 months. At 5 years, bRFS, cBR, and OS were 72 % (95 %CI: 61–81), 7 % (95 %CI: 3–14), and 82 % (95 %CI: 73–89), respectively. Twenty-nine patients experienced at least one late toxicity of grade ≥ 2; genitourinary (N = 29), including 3 cases of chronic hematuria, and/or gastrointestinal (N = 1). The cumulative incidence of late urinary toxicity of grade ≥ 2 was 20.6 % at 5 years (95 %CI: 13.9–28.1). Multivariate analysis revealed that a history of TURP was significantly associated with late urinary toxicity of grade ≥ 2, after adjusting for clinical target volume (Odds Ratio = 3.06; 95%CI: 1.05–8.86; P = 0.04). Conclusion: Extreme hypofractionated SBRT is effective for localized prostate cancer with a low risk of late toxicity. A history of TURP is associated with a higher risk of late urinary toxicity. These findings may contribute to the optimal management of patients treated with this regimen, particularly those with a history of TURP.